Reflections on Jews in Medieval Armenia and Armenian sources - Pogossian, Zaroui (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This article explores the presence of Jewish communities in Medieval Armenia in juxtaposition to mentions of Jews and Judaism in Medieval Armenian sources. It brings together the few notices of Jews living in Armenia and the neighboring Caucasian Albania based on P‘awstos Buzand, Movsēs Dasxuranc‘i, al-Balādhurī, Mas‘ud ibn Namdār, and Step‘anos Ōrbēlean and places this evidence against the background of many more sources that mention Jews and Judaism in different contexts and various categories of written sources regardless of living contact between Christian Armenian and Jewish populations. The argument is made to separate the images of Jews in the sources, including various rhetorical tools and literary tropes used to represent them that were typical of Christian cultures well beyond Armenia, from the presence of Jewish communities in Armenia. Indeed, the one medieval Jewish community in Armenian, in the village Ełegis, whose presence is attested beyond any doubt through material cultural evidence – a medieval Jewish cemetery – is not recorded in the written sources. Based on this premise, the final part of the article analyzes three hagiographical sources whose protagonists are Jews and formulates a hypothesis regarding the translation of each tale into Armenian and its possible purpose in the Armenian historical context with (or without) connection to relationships between Christian Armenians and Jews.